Cytochrome P450-epoxygenated fatty acids inhibit Müller glial inflammation - Cayla D. Ontko (Nature Portfolio, 2021)
Abstract Free fatty acid dysregulation in diabetics may elicit the release of inflammatory cytokines from Müller cells (MC), promoting the onset and progression of diabetic retinopathy (DR). Palmitic acid (PA) is elevated in the sera of diabetics and stimulates the production of the DR-relevant cytokines by MC, including IL-1β, which induces the production of itself and other inflammatory cytokines in the retina as well. In this study we propose that experimental elevation of cytochrome P450 epoxygenase (CYP)-derived epoxygenated fatty acids, epoxyeicosatrienoic acid (EET) and epoxydocosapentaenoic acid (EDP), will reduce PA- and IL-1β-induced MC inflammation. Broad-spectrum CYP inhibition by SKF-525a increased MC expression of inflammatory cytokines. Exogenous 11,12-EET and 19,20-EDP significantly decreased PA- and IL-1β-induced MC expression of IL-1β and IL-6. Both epoxygenated fatty acids significantly decreased IL-8 expression in IL-1β-induced MC and TNFα in PA-induced MC. Interestingly, 11,12-EET and 19,20-EDP significantly increased TNFα in IL-1β-treated MC. GSK2256294, a soluble epoxide hydrolase (sEH) inhibitor, significantly reduced PA- and IL-1β-stimulated MC cytokine expression. 11,12-EET and 19,20-EDP were also found to decrease PA- and IL-1β-induced NFκB-dependent transcriptional activity. These data suggest that experimental elevation of 11,12-EET and 19,20-EDP decreases MC inflammation in part by blocking NFκB-dependent transcription and may represent a viable therapeutic strategy for inhibition of early retinal inflammation in DR.